Analisa Vegetasi Gulma pada Pertanaman Jagung (Zea mays L) pada Lahan Olah Tanah Maksimal di Kabupaten Lima Puluh Kota - Bonna Suveltri; Zuhri Syam; - Solfiyeni (Universitas Andalas, 2014)
Research about the vegetation analysis of weeds in corn (Zea mays, L.) plantation in maximal prepared land in Lima Puluh Kota Regency had been conducted from October to November 2013 by using systematic squares method of 10 total plots with size1x1 m. It was found 563 individuals weeds, consist of 10 families, 18 genera and 18 species. Echinochloa crus-galii showed the highest value of SDR (Summed Dominance Ratio) (29.33%) and Zizania ceduciflora (0.77%) in maximal prepared land. The diversity index was H'= 1.558 (moderate). This land was dominated by wide-leaf group of weeds.Keywords: Weeds, corn, composition, structure, land